2020
DOI: 10.3390/antibiotics9100682
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Using Low-Concentration Oxacillin with Palmitic Acid and Span85 to Control Clinical Methicillin-Resistant Staphylococcus aureus

Abstract: The overuse of antibiotics has led to the emergence of multidrug-resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA). MRSA is difficult to kill with a single antibiotic because it has evolved to be resistant to various antibiotics by increasing the PBP2a (mecA) expression level, building up biofilm, introducing SCCmec for multidrug resistance, and changing its membrane properties. Therefore, to overcome antibiotic resistance and decrease possible genetic mutations that can lead to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Chan et al reported that two fatty acids from P. oleracea exhibited synergistic effects with erythromycin in combating MRSA ( Chan et al, 2015 ). Other organic acids from P. oleracea , such as protocatechuic and palmitic acids, also displayed effective bactericidal activity, which was in accordance with our results ( Chao and Yin, 2009 ; Song et al, 2020 ). Third, the inflammatory responses induced by S. aureus were used to evaluate the anti-inflammatory effects of OAPO.…”
Section: Discussionsupporting
confidence: 91%
“…Chan et al reported that two fatty acids from P. oleracea exhibited synergistic effects with erythromycin in combating MRSA ( Chan et al, 2015 ). Other organic acids from P. oleracea , such as protocatechuic and palmitic acids, also displayed effective bactericidal activity, which was in accordance with our results ( Chao and Yin, 2009 ; Song et al, 2020 ). Third, the inflammatory responses induced by S. aureus were used to evaluate the anti-inflammatory effects of OAPO.…”
Section: Discussionsupporting
confidence: 91%
“…Those that did not include relevant DMSO controls ( n = 38 articles) often used low concentrations (≤1% DMSO) to deliver treatments, which likely contributed to a reduced perceived need for a solvent control [ 47 , [51] , [52] , [53] , [54] , [55] ]. Studies that used higher DMSO concentrations without solvent controls were more concerning [ 49 , 50 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] as were studies that did not provide concentrations of DMSO used in treatments and did not include solvent controls [ 43 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. Media-only control-treated biofilms were frequently used in the calculations [ 50 , 56 , 57 , 78 , 79 ] although it is most appropriate to compare treatments delivered with DMSO to DMSO-only control-treated biofilms normalised to 100% growth as in [ 41 , [80] , [81] , [82] ].…”
Section: Resultsmentioning
confidence: 99%
“…A combination of propyl gallate (25 µg/mL) and octyl gallate (6.25 µg/mL) has been shown to improve the MIC of oxacillin against a panel of MRSA strains from 64-256 µg/mL to 2 µg/mL [15]. Palmitic acid (0.3-1.3 mg/mL) with surfactant Span85 (0.08-0.4%) with oxacillin (15-100 µg/mL) has been shown to inhibit the growth of a panel clinical MRSA strains in vitro [16]. ECG has been shown to possess a high affinity for the positively charged Staphylococcal membrane and induced changes to the biophysical properties of the bilayer that are likely to account for its capacity to disperse the cell wall biosynthetic machinery responsible for β-lactam resistance [17].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment and control regimens were initiated 2 h post-inoculation every 12 h two times daily for 2 days. All antimicrobials (0.1 mL) were administered subcutaneously [16,17]. Mortality of control and therapeutic groups were recorded during 48 h of therapy.…”
Section: Mouse Pneumonia Modelmentioning
confidence: 99%